Ecosystem services produced by groundwater dependent ecosystems: a framework and case study in California - Howard, Jeanette K.; Dooley, Katherine; Brauman, Kate A.; Klausmeyer, Kirk R.; Rohde, Melissa M. (Frontiers in Water, 2023)
Groundwater is an important freshwater supply for agricultural, domestic, and environmental uses and critical buffer against a warming climate, particularly in semi-arid and arid regions of the world. Groundwater dependent ecosystems (GDEs), which rely on groundwater for some or all of their water requirements, include terrestrial vegetation, rivers, springs, wetlands, and riparian zones. These GDEs provide benefits to people ranging from habitat for pollinators to carbon sequestration. Accounting for these benefits, called ecosystem services, can inform management by expanding the potential group of groundwater users to include groundwater dependent ecosystems. Here we develop an approach to inventory the ecosystem services of GDEs by identifying the ecosystem functions of a range of GDEs and assessing how they are linked to a wide range of ecosystem services. We apply this approach as a case study in California, USA, where we found ecosystem services from GDEs is widespread across the state; over 30% of California's pollinator dependent crops may benefit from GDEs, and carbon storage of GDEs is equivalent to 790 million tons, twice as much as California emits annually.